Team-Based Oncology Care: The Pivotal Role of Oncology Navigation (Springer International Publishing, 2018)
This book discusses how effective navigation requires a team approach to oncology care and should never be considered an "add-on" resource or service. The Academy of Oncology Nurse & Patient Navigators (AONN) is the only national professional organization for navigation professionals, and has more than 6,000 members, 90% of which are oncology nurse navigators. They are the experts on creating team-based programs, which remove the risk of others trying to reinvent the wheel by designing a navigation program from scratch. They also understand the role of effective navigation across the entire continuum of care, and understand and are able to apply other key aspects of navigation, including clinical trial screenings and tumor board coordination and monitoring, as well as measurement using evidence-based navigation metrics, to name but a few. It is the only book designed to educate and support anyone developing a new navigation program, or wanting to improve one they have created. As such it offers a guide for cancer centers needing to develop and implement an oncology navigation program; understand and successfully meet and exceed the Commission on Cancer accreditation standards linked to navigation; expand or improve their current navigation program as well as demonstrate its value using reliable measurable results, including patient satisfaction and improved- quality clinical outcomes. This comprehensive book also provides insights into applying the information presented to the real world of oncology care.